2004
DOI: 10.1071/ap03093
|View full text |Cite
|
Sign up to set email alerts
|

Rhizoctonia crown and root rot of the pasture legume, sulla (Hedysarum coronarium)

Abstract: Abstract. Rhizoctonia solani AG-2-2 was isolated from wilting and dying plants of sulla (Hedysarum coronarium), which is currently being assessed in eastern and southern Australia for its potential as a pasture and forage legume. Infected plants in the field had extensive rotting of the taproot, lateral roots and crown. Koch's postulates were fulfilled using three inoculation methods. The disease may pose a considerable threat to the potential use of H. coronarium in the dryland, grazing farming systems of Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…). These observations are consistent with the symptoms described for the R. solani ZG1‐1 (AG8) isolate infecting canola (Khangura et al ., ) and R. solani AG2‐2 isolates infecting the pasture legume Hedysarum coronarium (Ryley et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…). These observations are consistent with the symptoms described for the R. solani ZG1‐1 (AG8) isolate infecting canola (Khangura et al ., ) and R. solani AG2‐2 isolates infecting the pasture legume Hedysarum coronarium (Ryley et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…While R. solani ZG4 (AG2-2) has been reported to cause hypocotyl rot on legumes (Sweetingham et al 1986) and soybean (Glycine max [L.] Merr.) (Fenille et al 2004), AG2-2 has been reported causing crown and root rot of H. coronarium in Queensland, Australia (Ryley et al 2004), root rot of subterranean clover (Wong and Sivasithamparam 1985;MacNish et al 1994 (Sumner 1985); wheat (T. aestivum) and barley (Furgal-Wegrzycka et al 1998); and several grasses (Haygood and Martin 1990;Herr and Fulton 1995).…”
Section: Discussionmentioning
confidence: 98%
“…(You et al 1999;Barbetti et al 2006) and more recently has been reported to cause severe root disease on several newly introduced legume species including Hedysarum sp. (Ryley et al 2004). This marked increase in root rots affecting pasture legumes in recent years, including diseases caused by R. solani, may be related to the increasing frequency of the leguminous host in the rotation system in recent years, leading to enrichment of pathogens of legumes in pasture-crop rotations.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation